Manifestasi perceraian orang tua dalam kepuasan hubungan berpacaran pada emerging adulthood - Novelia Tarizka Putri; Diana Permata Sari (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2026)
The phenomenon of parental divorce has the potential to shape commitment, trust, and intimacy with a partner during emerging adulthood. This study aims to understand how parental divorce manifests in dating relationship satisfaction during emerging adulthood. A qualitative method with a phenomenological design was used to explore subjective meanings. The study included three informants selected through purposive sampling in accordance with predetermined criteria. Data were collected through semi-structured interviews and analyzed using reflexive thematic analysis. The main themes identified include (i) family and partners as secure attachment figures, (ii) positive evaluations of dating relationships, (iii) communication in fostering relational closeness, and (iv) constructive conflict resolution. Additionally, gender-based differences were found regarding the needs they sought to fulfill to achieve relationship satisfaction. Female informants emphasized emotional needs, while male informants emphasized acceptance within the relationship. The experience of parental divorce does not always manifest negatively but can serve as a source of learning in building trust and closeness with a partner. Fenomena perceraian orang tua berpotensi membentuk komitmen, kepercayaan dan kedekatan dengan pasangan pada emerging adulthood. Penelitian ini bertujuan untuk memahami bagaimana perceraian orang tua termanifestasi dalam kepuasan hubungan berpacaran pada masa emerging adulthood. Metode kualitatif dengan desain fenomenologi dipakai untuk mengeksplorasi makna subjektif. Informan penelitian berjumlah tiga orang yang dipilih melalui teknik purposive sampling sesuai dengan kriteria yang sudah ditetapkan. Data dikumpulkan melalui wawancara semi-terstruktur dan dianalisis dengan analisis tematik reflektif. Tema utama yang ditemukan meliputi (i) keluarga dan pasangan sebagai figur kelekatan aman, (ii) penilaian positif dalam hubungan berpacaran, (iii) komunikasi dalam mengembangkan kedekatan relasional, (iv) serta resolusi konflik konstruktif. Selain itu, ditemukan perbedaan berdasarkan gender mengenai kebutuhan yang ingin dipenuhi dalam membentuk kepuasan dalam hubungan. Informan perempuan menekankan kebutuhan emosional, sedangkan laki-laki menekankan penerimaan dalam hubungan. Pengalaman perceraian orang tua tidak selalu termanifestasi secara negatif tetapi dapat menjadi sumber pembelajaran dalam membangun rasa kepercayaan dan kedekatan dengan pasangan.